2008
DOI: 10.1093/glycob/cwn104
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 functions as an opsonin and enhances the macrophage clearance of apoptotic neutrophils

Abstract: Galectin-3, a beta-galactoside binding, endogenous lectin, takes part in various inflammatory events and is produced in substantial amounts at inflammatory foci. We investigated whether extracellular galectin-3 could participate in the phagocytic clearance of apoptotic neutrophils by macrophages, a process of crucial importance for termination of acute inflammation. Using human leukocytes, we show that exogenously added galectin-3 increased the uptake of apoptotic neutrophils by monocyte-derived macrophages (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 18 publications
2
111
0
3
Order By: Relevance
“…Moreover, MacKinnon et al have shown that up-regulation of galectin-3 expression is a feature of the alternative macrophage (M2) phenotype and that release of galectin-3 by alternatively activated macrophages sustains the M2 phenotype contributing to some of its functions in vivo [68]. For instance, Karlsson et al showed that galectin-3, by functioning as an opsonin, favors the phagocytic clearance of apoptotic neutrophils by macrophages, a process of crucial importance for termination of acute inflammation [69]. Accordingly, Caberoy et al have recently demonstrated that galectin-3 is a legitimate MerTK-specific "eat-me" signal which stimulates phagocytosis of apoptotic cells and cellular debris [70].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 99%
“…Moreover, MacKinnon et al have shown that up-regulation of galectin-3 expression is a feature of the alternative macrophage (M2) phenotype and that release of galectin-3 by alternatively activated macrophages sustains the M2 phenotype contributing to some of its functions in vivo [68]. For instance, Karlsson et al showed that galectin-3, by functioning as an opsonin, favors the phagocytic clearance of apoptotic neutrophils by macrophages, a process of crucial importance for termination of acute inflammation [69]. Accordingly, Caberoy et al have recently demonstrated that galectin-3 is a legitimate MerTK-specific "eat-me" signal which stimulates phagocytosis of apoptotic cells and cellular debris [70].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 99%
“…Gal-3 has been found to play a critical role in macrophage phagocytosis with Gal-3 null macrophages demonstrating decreased phagocytosis of IgG-opsonised erythrocytes and thymocytes in vitro; moreover, Gal-3 null mice display reduced phagocytosis of red blood cells by kupffer cells in a model of haemolytic anaemia (Sano et al 2003). Treatment with hr-Gal-3 increases phagocytosis of apoptotic neutrophils by monocyte-derived macrophages (Karlsson et al 2008), and this is in agreement with the fact that Gal-3 null macrophages demonstrate reduced phagocytosis of apoptotic neutrophils . As well as increasing macrophage phagocytosis, Gal-3 also enhances the phagocytic capabilities of neutrophils, a fact that may in part account for the protective role of Gal-3 in infections such as S. pneumoniae .…”
Section: Actions Of Exogenous Galectin-3mentioning
confidence: 99%
“…Apoptotic neutrophils display a distinct surface molecular phenotype important for attenuation of functional responses (9) with additional surface changes that target dying cells for removal by phagocytes (10). A number of soluble factors present in serum, including complement C1q and C3b, properdin, collectins, long pentraxin-3, MFG-E8, galectin-3, and ␣ 2 -macroglobulin, have been reported to bind to apoptotic human cells (11)(12)(13)(14)(15)(16)(17)(18) and consequently modulate their recognition and uptake by macrophages via a number of different surface receptors, including scavenger receptors, complement receptors, receptors for phosphatidylserine, and Mertk (19 -22). However, it is important to note that some of these opsonization events occur relatively late during the apoptotic process and accompany loss of membrane integrity (23).…”
mentioning
confidence: 99%